Rivaroxaban in stroke prevention in patients with non-valvular atrial fibrillation: what facts are important for the clinician? - I. S. Yavelov (Рациональная фармакотерапия в кардиологии)
The article discusses the results of randomized controlled trials and some observational studies that define the current understanding of the role of rivaroxaban in the prevention of cardioembolic complications in patients with atrial fibrillation (AF). According to the results of the randomized controlled trial ROCKET AF, in patients with non-valvular AF, rivaroxaban is at least as effective as warfarin. At the same time, while the rates of major and clinically significant non-major bleeding were comparable, fatal bleeding and bleeding in critical organs (including intracranial bleeding) were less frequent in the rivaroxaban group, whereas clinically relevant gastrointestinal bleeding occurred more often. Overall, the rate of major gastrointestinal bleeding increased by 10 cases per 1,000 treated patients per year in the rivaroxaban group, and its occurrence did not lead to the need for large-volume blood transfusions or an increased risk of death. Similar clinical effects can be expected in various patient categories, including those with impaired kidney function (down to a creatinine clearance of 15 mL/min) and elderly patients. According to accumulated evidence, rivaroxaban reduces the risk of coronary thrombosis after coronary stenting and should be combined with one antiplatelet agent (mainly clopidogrel) in this case. According to the results of the X-VERT study, rivaroxaban appears to be an effective and safe alternative to vitamin K antagonists during cardioversion and may allow for rapid cardioversion in hemodynamically stable patients with paroxysmal non-valvular AF. Due to the lack of an available laboratory monitoring method and significant variations in drug concentration in the blood among those receiving rivaroxaban, studies on bioequivalence with determination of anti-Xa activity in the blood are particularly important for its generics. Data on the similar composition of tablets, comparable dissolution kinetics and bioequivalence are available, in particular, from the Russian generic rivaroxaban Zinacoren.